HLA-DP and coeliac disease: family and population studies. Issue 6 (June 1990) - Caffrey, C; Hitman, G A; Niven, M J; Cassell, P G; Kumar, P; Fry, L; Mackintosh, P; Gallagher, R; Feighery, C; Weir, D
Abstract : We investigated polymorphism of HLA-DP genes in three DR3 related diseases, confirming an association of coeliac disease with a Bgl II DP alpha polymorphism (a restriction fragment sized 3.5 kb present in 75% of patients compared to 34% of control subjects, p less than 0.001), and finding a weaker association with dermatitis herpetiformis (57% v 34%, p = 0.01) and no association with insulin dependent diabetes mellitus. The association with coeliac disease was further investigated. Msp I DP beta polymorphism was studied in 52 healthy subjects and 59 patients: a 4.9 kb fragment was present in 51% of patients with coeliac disease compared to 11.5% of control subjects (p less than 0.001). Furthermore, nearly all subjects with the DP alpha 3.5 kb fragment also had the DP beta 4.9 kb fragment. However, disease frequency was still increased in the DP alpha 3.5 positive/DP beta 4.9 negative group. In seven families, each with at least two affected members, while the DP alpha 3.5 fragment was frequently present in patients it did not preferentially segregate with any particular HLA haplotype–for example, those associated with DR3 or DR7–and therefore is not part of an extended haplotype associated with coeliac disease. We therefore conclude that a gene(s) in the HLA-DP region predisposes to coeliac disease independently of the HLA-DR/DQ regions.